VALIDITY LEVEL OF 3D PAGEFLIP POCKET BOOK ABOUT SPECIES ON CYPERACEAE FAMILY AT GALAM VEGETATED SWAMP - Siti Sarah; Dharmono Dharmono; Maulana Khalid Riefani (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Local potential in South Kalimantan, especially plants, can be used as a source of learning. Valid learning resources are learning resources that are validated by experts. Validation can be interpreted as an act of proof appropriately through certain stages to always achieve the desired results. The purpose of this study was todesribe the validity of the 3D pageflip based pocket book of the Cyperaceae Family in the Galam Vegetated Swamp, Bati-Bati District. This research method uses Education Design Research (EDR) with the Tessmer formative evaluation model by 2 experts. The results of the validation stage research by 90,97% of experts with the criteria “very valid” so that it can be used as a learning resorce.